2016
DOI: 10.1016/j.enbuild.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Economic feasibility study of a fuel cell-based combined cooling, heating and power system for a data centre

Abstract: a b s t r a c tThe energy use of data centres is increasing as the data storage needs increase. One of the largest items in the energy use of these facilities is cooling. A fuel cell-based combined cooling, heating and power system can efficiently meet such a centre's need for cooling and in the meantime generate enough electricity for the centre and more. In this paper the economic feasibility of a fuel cell-based combined cooling, heating and power system that meets the energy demands of such a facility is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…This demonstrates the second key feature of DCP-IESs: high carbon emissions. Additionally, IDCs exhibit a cascade energy use structure, e.g., IT equipment generally consumes high-grade energy, whereas cooling equipment uses low-grade energy [9]. Data center energy consumption involves not only consumption from web servers and private branch exchanges but also consumption from air conditioning systems (ACS), power distribution units, uninterrupted power supplies (UPS), and illuminating and switching units [4].…”
Section: Dcp-iess and Their Key Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This demonstrates the second key feature of DCP-IESs: high carbon emissions. Additionally, IDCs exhibit a cascade energy use structure, e.g., IT equipment generally consumes high-grade energy, whereas cooling equipment uses low-grade energy [9]. Data center energy consumption involves not only consumption from web servers and private branch exchanges but also consumption from air conditioning systems (ACS), power distribution units, uninterrupted power supplies (UPS), and illuminating and switching units [4].…”
Section: Dcp-iess and Their Key Characteristicsmentioning
confidence: 99%
“…This demonstrates the second key feature of DCP-IESs: high carbon emissions. Additionally, IDCs exhibit a cascade energy use structure, e.g., IT equipment generally consumes high-grade energy, whereas cooling equipment uses low-grade energy [9]. Table 1.…”
Section: Dcp-iess and Their Key Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sevencan et al [50] carried out an economic study on the use of an MCFC coupled with VARS for data centre cooling and concluded that the system was not economically feasible due to high capital and Operational & Maintenance (OM) costs and also that the lifetime of the current MCFC stacks was too short. This was a pure economical study and no technical details, besides the type of the MCFC (DFC300 from Fuel Cell Energy), were provided.…”
Section: Absorption Refrigeration Systems Coupled To Fuel Cellsmentioning
confidence: 99%
“…The early studies of CCHP system optimization mainly focus on the system cost minimization [6][7][8][9][10]. Recently, researchers have started to consider system reliability and environmental sustainability, in addition to the system cost [4,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%